Hermeneutika sebagai Teori Kritik Teks Sastra dan Keagamaan: Perbandingannya dengan Ta’wil - Sukron Kamil (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
Since the polarization between liberal Islam exponent and the conservative Islam circle happened, hermeneutic become very popular among literate Moslem in Indonesia. For conservative circle, Islamic liberal opinions like pluralism, liberalism, secularism, and marriage in different religion begin from using of hermeneutic. Hermeneutic even also looked into dangerous in interpreting Qur’an or hadith. Though, there are proportionate ta’wil by hermeneutic in Islam, what up to now still become the part of traditional science of Islam. This Article find that much similarity between west modern theory of hermeneutic and ta’wil in tradition of Islam or Arab. As a modern hermeneutic, theory of ta’wil with its typology tend to subjective, even relative. There is also very taking care of objectivity by emphasizing text as base (agreed in language), context, and its author context. There is a moderate theory which though take care of the objectivity of text, but do not deny that result of ta’wil is not sterile at all from relativity element. In consequence, it is difficult to be said that hermeneutic is the non-Islamic west theory, and the primary factor of contemporary conservative circle deduction to hermeneutic in fact is its literal tendency.